MENINGKATKAN KEMAMPUAN MEMBACA CERITA CEKAK MELALUI PENGUASAAN KOSA KATA BAHASA JAWA SISWA KELAS VIII SMPN 8 SURAKARTA - Sri Suprapti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2018)
This study examines how reading in Javanese short story is improved by the mastery of Javanese vocabulary.  The study used Classroom Action Research that implemented two cycles, each of which consisted of three meetings.  The research was conducted in the ninth graders of SMPN 8 Surakarta involving 32 students. The results who that students improve their ability in reading comprehension of Javanese short story substantially.  Results of test comprehension on reading Javanese short story, task to evaluate short study aspects applied fro Javanese short story and effectiveness of classroom activities improve at two cycles, gaining minimum criteria of score that is higher than 75 and classical teaching of 85%.   It implies that the function of Javanese vocabulary is pivotal to improve students mastery in reading Javanese texts and provide patterns of how Javanese is implemented.